Quality Assessment of Library Website of Iranian State Universities: - Farideh Osareh; Zeinab Papi (Iranian Journal of Information Processing & Management, 2008)
The present study carries out a quality assessment of the library websites in Iranian State Universities in order to rank them accordingly. The evaluation tool used is the normalized Web Quality Evaluation Tools (WQET). 41 Active library websites were studied and assessed qualitatively over two time periods (Feb 2006 and May 2006) using WQET. Data were collected by direct observation of the website. The evaluation was based on user characteristics, website purpose, upload speed, structural stability, ease of searching, graphic design, availability of authors’ c.v., clear objectivity, update and internal links. Website ranking showed that the website libraries for the Iran University of Science and Technology and Mazandaran University ranked first by obtaining 82 points out of 82 points. These were followed by the library websites of University of Tehran, Imam Sadegh University, Gilan University and Tarbiyat Moddaress University.